Notes on the pure spinor b ghost - Jusinskas, Renann Lipinski [UNESP] (Springer Nature, 2013)
In this work, a particular BRST-exact class of deformations of the b ghost in the non-minimal pure spinor formalism is investigated and the impact of this construction in the N= 2 ĉ = 3 topological string algebra is analysed. As an example, a subclass of deformations is explicitly shown, where the U (1) current appears in a conventional form, involving only the ghost number currents. Furthermore, a c ghost like composite field is introduced, but with an unusual construction. © 2013 SISSA, Trieste, Italy.
Keywords: Superstrings and Heterotic Strings; Topological Strings